"Skills come with experience" a pedagogical study of different forms of communication in Nenets nomadic communities in Northern Russia. (February 2021) - Ravna, Zoia Vylka
Abstract: This article raises the issue of child rearing techniques used by Nenets mothers in the nomadic conditions of the Arctic Tundra. The focus of the article is a description and analysis of different types of inter-generational communication in the process of the training of basic skills and abilities that children of tundra nomads need to possess in order to become Tenevana (knowledgeable). The theoretical framing of this study is the theory of indigenous teachers "labour education within the family". The analytical approach of this study is structured within an interdisciplinary methodology and is based on methods of in-depth-interviews, questionnaires and fieldwork. Based on an analysis of the rich array of the data produced, the author has concluded that the most important forms of communications are also the most vulnerable: such as folklore and storytelling. Highlights: Ethnic pedagogy has not yet recognized traditional Nenets methods of knowledge transmission. Different forms of communications are systematic and effective means of raising children in the Tundra. Independence of thinking, speed in decision making and originality of approaches to solving problems. Many forms of communications, oral stories and storytelling are rapidly disappearing.